Pengaruh Strategi Promosi Melalui Voucher TikTok Dan Kualitas Media Sosial Terhadap Peningkatan Penjualan Pada “Cafe Bagi Kopi” Pamulang Tangerang Selatan - Aulia Jihan Kamalia; Farrah Dwi Ramadhani; Nasywaa Khairunnisaa; Salwa Ramadhanti; Derizka Inva Jaswita (PT. Hasba Edukasi Mandiri, 2025)
The rapid development of digital technology and social media has encouraged changes in marketing strategies within the culinary business sector, particularly through the use of the TikTok platform. One widely applied form of digital marketing is promotion through TikTok vouchers and the presentation of high-quality social media content to attract consumer interest. This study aims to analyze the effect of promotional strategies through TikTok vouchers and the quality of social media content on sales increase at Cafe Bagi Kopi Pamulang, Tangerang Selatan. This research employs a quantitative approach with an associative method. The population of this study consists of consumers of Cafe Bagi Kopi Pamulang who have made purchases through TikTok promotions, with a sample of 100 respondents selected using purposive sampling techniques. Data were collected through a Likert scale-based questionnaire, while data analysis techniques included validity testing, reliability testing, classical assumption tests, multiple linear regression analysis, t-test, F-test, and coefficient of determination (R²) using SPSS software. The results indicate that partially, promotional strategies through TikTok vouchers have a significant effect on sales increase, and the quality of social media content also has a significant effect on sales increase. Simultaneously, promotional strategies through TikTok vouchers and the quality of social media content have a significant influence on sales increase at Cafe Bagi Kopi Pamulang. These findings provide practical implications for culinary business owners to optimize digital promotional strategies and improve social media content quality in order to enhance sales performance and business competitiveness.